Further investigation on "A multiplicative regularization for force reconstruction". (1st May 2018) - Aucejo, M.; De Smet, O.
Highlights: A further investigation on "A multiplicative regularization for force reconstruction problems" is introduced. A full resolution algorithm is presented and validated numerically and experimentally. A detailed comparison with the original algorithm is proposed. This paper aims at clarifying the derivation of the original resolution algorithm. Abstract: We have recently proposed a multiplicative regularization to reconstruct mechanical forces acting on a structure from vibration measurements. This method does not require any selection procedure for choosing the regularization parameter, since the amount of regularization is automatically adjusted throughout an iterative resolution process. The proposed iterative algorithm has been developed with performance and efficiency in mind, but it is actually a simplified version of a full iterative procedure not described in the original paper. The present paper aims at introducing the full resolution algorithm and comparing it with its simplified version in terms of computational efficiency and solution accuracy. In particular, it is shown that both algorithms lead to very similar identified solutions.